If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25y(3y + 2x) = 0 Reorder the terms: 25y(2x + 3y) = 0 (2x * 25y + 3y * 25y) = 0 (50xy + 75y2) = 0 Solving 50xy + 75y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75y2' to each side of the equation. 50xy + 75y2 + -75y2 = 0 + -75y2 Combine like terms: 75y2 + -75y2 = 0 50xy + 0 = 0 + -75y2 50xy = 0 + -75y2 Remove the zero: 50xy = -75y2 Divide each side by '50y'. x = -1.5y Simplifying x = -1.5y
| 3x/4-1/2=1/4 | | -6g+22=-3g+8g | | -7x+1=7x-139 | | 72-2x-3=46 | | -8(1+8k)-8k=-8-5k | | -10+6+2x=100 | | 72x-2x-3=46 | | -9g+30=-6g+7g | | (3x-3)+3(4x+8)=4x-1 | | 0.44(x+6)=8 | | 1/8=1/1/8/n | | 7w+2w-1=4w+9 | | 15x=3(4x+24) | | N-6=2*4 | | f(x)=0.97+4.5x | | 3x-2(x-1)=-4+3x+10 | | 8=-(-6+n) | | N-6=2*8 | | 6+x+3x=-16 | | 13x=3(2x+28) | | 2(x+4)=32+5x | | (5x+13)=72 | | 14-7p=-7(p-1) | | 14x=3(2x+72) | | (5-3)x(-2)= | | 136=-8(1+6V) | | 14-7p=-7p(p-1) | | 3a-7z=6 | | (12x-8)= | | -6g+30=6 | | .30/(y-1.43)=x | | r+441=-225 |